Peningkatan Kapasitas Tanggap Bencana pada Siswa SMA Adabiah Padang - Esi Afriyanti; Reni Prima Gusty (Warta Pengabdian Andalas, 2022)
The city of Padang has a topography that is prone to flooding or inundation and other natural disasters such as earthquakes and tsunamis. The city of Padang, which is located on the collision of the Indian Ocean Plate and the Australian Plate, which infiltrates under the Eurasian Plate, forms the Benioff Zone, an earthquake zone with seismicity of magnitude greater than five on the Richter scale. With the condition of the city of Padang, which is prone to disasters, community participation is very much needed, especially at the pre-disaster stage (disaster mitigation), during emergency response, and post-disaster because the community is directly dealing with disasters. Schools play an essential role and have several functions in disaster risk reduction including facilitating and collaborating with the surrounding environment, improving community skills, refugee shelter centres when a disaster occurs. Therefore, it was necessary to carry out activities that can increase the understanding and expertise of the young school community, especially students in disaster mitigation and disaster response. On November 12, 2021, this activity was held at SMA Adabiah Padang with 21 students. The methods used in the activity were disaster counselling, triage concept, vital sign monitoring and splinting. The activity results found an increase in student's knowledge after being given health education and increased students' abilities in triage and splinting.